2001
DOI: 10.1002/chir.1022
|View full text |Cite
|
Sign up to set email alerts
|

First direct discrimination of chiral phosphorus thionate (P=S) derivatives by multinuclear magnetic resonance spectroscopy in the presence of a chiral dirhodium complex

Abstract: Enantiomeric ratios of compounds with P=S functionalities can be determined by 1H, 13C, and 31P NMR spectroscopic inspection of their diastereomeric complexes with (R)-Rh2(MTPA)4 (MTPA-H identical with methoxytrifluoromethylphenylacetic acid; Mosher's acid). This is the first facile and rapid spectroscopic method for chiral recognition in this class of compounds. Whereas complexation shifts Deltadelta are moderate or even negligible, significant signal dispersions Delta(nu) can be observed. Some rationalizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2002
2002
2005
2005

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 30 publications
2
12
0
Order By: Relevance
“…In accordance with our previous observations for other ligands, 5,6 Dd-values are small (<0.5 ppm) or even negligible for 1 H signals. They are larger for 13 C (up to )4 ppm) and 31 P (up to +5.9 ppm), a fact which is expected, considering the much larger chemical shift range of these two nuclei.…”
Section: Complexation Shifts Ddsupporting
confidence: 92%
See 1 more Smart Citation
“…In accordance with our previous observations for other ligands, 5,6 Dd-values are small (<0.5 ppm) or even negligible for 1 H signals. They are larger for 13 C (up to )4 ppm) and 31 P (up to +5.9 ppm), a fact which is expected, considering the much larger chemical shift range of these two nuclei.…”
Section: Complexation Shifts Ddsupporting
confidence: 92%
“…In our experience, 5,6,11 acetone does not significantly compete with the ligands in adduct formation.…”
mentioning
confidence: 77%
“…Standards were internal TMS (υ D 0) for 1 H and for 13 C, and external (PhSe) 2 (υ D 463) corresponding to (CH 3 All samples were prepared by mixing 45.2 mg (0.04 mmol) of Rh-Rh and the appropriate molar equivalent of the respective selenide in 0.7 ml of CDCl 3 , adding 7 µl (1 drop) of acetone-d 6 to increase the solubility of Rh-Rh. 4,5 The concentrations in the probes of the free ligands were similar.…”
Section: Nmr Measurementsmentioning
confidence: 95%
“…Therefore, we call the difference of the chemical shifts in these adducts as compared to the corresponding values of the free ligands "adduct formation shifts," ⌬␦ (in ppm). It should be noted that, according to our previous work on dirhodium adducts with related ligands, [1][2][3] it can be gen- erally assumed that the experimental set-up (1:1 molar ratio) leads to a predominance of 1:1-adducts in the equilibrium, as shown in Scheme 2. 4 The ligands 1-12 are chiral and the compounds exist as racemates, whereas Rh* is enantiopure.…”
Section: -Methyl-1-phenyl-3-phospholene 1-selenide (6)mentioning
confidence: 99%
“…1 Very recently, we reported that this "dirhodium method" is the only direct technique for chiral phosphine sulfides (P=S) 2 and phosphine selenides (P=Se). 3 In continuation of our studies we investigated a series of cyclic phospholenechalcogenides 1-11 and one phospholane oxide 12 (Scheme 1).…”
Section: P Nmrmentioning
confidence: 99%